Research, policy an practice - worlds apart? - Locock, Louise; Boaz, Annette (2004)
The relationship between research, policy and practice remains a contested area. This article explores pressures for researchers to make their work more useful and relevant to policy and practice, and for practitioners to undertake research. Whilst there are clearly areas of mutual interest and benefit, we argue that the research, policy and practice communities also have distinct traditions, skills and obligations which should be recognised and valued rather than artificially suppressed. Narrow conceptions of research utility constrain the debate about what each community has to offer and how best to communicate with each other across borders. - Reproduced.
Keywords: Research